PEMBERDAYAAN USAHA JAMU JAHE INSTAN DI KOTA SURAKARTA DAN KABUPATEN SUKOHARJO MELALUI TEKNOLOGI PENGOLAHAN JAHE - Muttaqin, Hermansyah; Cahyadin, Malik; Widiyanti, Emi (Universitas Negeri Yogyakarta, 2015)
This activity aims to increase ginger herbal medicine business in Surakarta and Sukoharjo through: improvement of the quality and quantity of production, improvement of business management, and improvement of business financial bookkeeping. Partners of this activity are SMEs of herbal ginger